PENGARUH MEDIA TERHADAP PERTUMBUHAN LARVA MAGGOT (Hermetia illucens) SEBAGAI SUMBER BELAJAR BIOLOGI BERUPA LEMBAR KEGIATAN PESERTA DIDIK - Ditha Mellynia Putri; Widya Sartika Sulistiani; Suharno Zen (EDUBIOLOCK, 2024)
One of the problems that exist in the Cendrawasih market in Metro City is market waste in the form of vegetable waste and fruit waste because of the odr I cause, besides ha I have an impact on human health, the environment, and socio-economics. So, to reduce the amount of waste piled up, you can use it by cultivating maggots. This research aims (1) to determine the effect of various media on the growth of maggot larvae (Hermetia illucens), (2) to determine the media that provide the best influence on the growth of maggot larvae (Hermetia Illucens), and (3) to determine whether the results are suitable as a student worksheet (LKPD). The type of research was quantitative using experimental research design and a Completely Randomized Design (CRD) method with 4 treatments, each with 3 replications. 4 treatments are (P0): 500 g of oil palm meal, (P1): 500 g vegetable waste, (P2): 500 g fruit waste, and (P3): 250 g vegetable waste + 250 g fruit waste. The research used 7 days old of maggot larvae. This research was conducted for 20 days 38B Banjar Rejo. Based on the weight of maggot larvae and the final weight growth media, the best growth media is (P3) with 250 g of vegetable waste + 250 g of fruit waste. The results of this research can be used as a student worksheet resource in the form of a class.